Hacia una revitalización de los usos lingüísticos del dialecto andaluz en la enseñanza de la lengua materna en Andalucía: una propuesta didáctica para la E.S.O. - Cantero Garcia, Víctor (Didáctica. Lengua y Literatura, 2010)
In this article, the reader is offered a didactic proposal to start the teaching of the Andalusian dialect in Secondary Education. According to the suggestions made to Secondary teachers by the Andalusian Educational Administration, the author reflects on the need to promote the Andalusian youngsters´ linguistic awareness of their way of speaking: the Andalusian dialect. The above thought implies a number of didactic exercises which will be very useful to those teachers who pretend to boost the teaching of the Andalusian dialect as an identifying mark of their region.